Las TIC’S y su aporte en el desarrollo de las capacidades cognitivas a los estudiantes de bachillerato de la Unidad Educativa Barreiro Parroquia Barreiro, cantón Babahoyo, Provincia Los Ríos - Tapia Arévalo, Luis Stalyn (2019)
In the Barreiro educational unit after research we found that the institution has a problem that refers to the development of cognitive abilities of students in the baccalaureate area due to the lack of technological tools within the institution and classrooms with this research we will give a solution to the previously raised after a study and the identification of the problems of the institution, we propose the main objective that will be to determine what influences have the information and communication technologies within the classroom and the institution, the type Research that helped me to start my project is descriptive research, because through the information obtained will describe the information and communication technologies and their consequences in the development of cognitive abilities in students; allowing us to make a diagnosis to constitute the main element in the realization of an investigation because without it it would be practically impossible to bring to fruition and with positive results of research related to the improvement of some situation. The method we use in our research is the Hypothetical-Deductive because it has several essential steps: observation of the phenomenon to be studied, creation of a hypothesis to explain this phenomenon, deduction of consequences or propositions more elementary than the hypothesis itself, and verification or verification of the truth of the statements deduced The study applies the techniques of observation since it is necessary to visit the place of study, and surveys to teachers and students of the Barreiro Educational Unit, indirect observation that will allow to select what will be necessary for the analysis of the possible causes that originated the problem, in addition to how the professional performance of the teachers is evolving and in this way it is possible to diagnose the effects that originate if an early intervention is not made, for the application of ICT. The population to study is a total of 391 people taking as sample 125 people including teachers and students. The current final report is aimed at carrying out a study of the professional performance support of the information and communication tools in the teachers and assessing the need to propose a manual to improve the skills in this use for the Barreiro Educational Unit. To this end, a theoretical framework was prepared on the main characteristics that make up a manual, its elements, the basic knowledge it must have and the additional multimedia tool.